Studies of 2D Bulk and Nanoribbon Band Structures in MoxW1–xS2 Alloy System Using Full sp3d5 Tight‐Binding Model. Issue 2 (18th September 2020) - Tsai, Tsung-Yin; Chen, Pin-Fang; Chang, Shu-Wei; Wu, Yuh-Renn
Abstract : A full sp 3 d 5 tight‐binding model (TBM) is used to calculate the band structure of Mo x W1– x S2 alloy monolayers and armchair nanoribbons. First, the parameters required for the alloy system are extracted from density functional theory. Then, TBM is used to enable a larger computational domain for the alloy system. Herein, the electronic properties of Mo x W1– x S2 alloys, such as the band structure, bandgap, and density‐of‐states effective mass, are determined computationally. These properties could be useful in the design of future devices. Abstract : The electronic properties of Mo x W1– x S2 alloy monolayer and armchair nanoribbons are investigated using the full sp 3 d 5 tight‐binding model (TBM). The way to extract TBM parameters of Mo x W1– x S2 alloy from density functional theory is presented. The band structure, bandgap, density‐of‐states, and effective masses as a function of Mo composition are calculated in this work.